2015
DOI: 10.1038/srep11559
|View full text |Cite
|
Sign up to set email alerts
|

iRhom1 regulates proteasome activity via PAC1/2 under ER stress

Abstract: Proteasome is a protein degradation complex that plays a major role in maintaining cellular homeostasis. Despite extensive efforts to identify protein substrates that are degraded through ubiquitination, the regulation of proteasome activity itself under diverse signals is poorly understood. In this study, we have isolated iRhom1 as a stimulator of proteasome activity from genome-wide functional screening using cDNA expression and an unstable GFP-degron. Downregulation of iRhom1 reduced enzymatic activity of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 47 publications
1
33
0
Order By: Relevance
“…9C,D). It was previously reported that miR-126 targets 3Ј-UTR of TOM1 mRNA to regulate its expression and may be involved in several neuropsychiatric disorders (Oglesby et al, 2010;Sonntag et al, 2012; and that miR-126 expression potentiates A␤ toxicity (Kim et al, 2016). Thus, we attempted to identify whether miR-126 regulated TOM1 level in AD model.…”
Section: Tom1 Level Is Regulated By Mir-126-3p and Crucial For Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…9C,D). It was previously reported that miR-126 targets 3Ј-UTR of TOM1 mRNA to regulate its expression and may be involved in several neuropsychiatric disorders (Oglesby et al, 2010;Sonntag et al, 2012; and that miR-126 expression potentiates A␤ toxicity (Kim et al, 2016). Thus, we attempted to identify whether miR-126 regulated TOM1 level in AD model.…”
Section: Tom1 Level Is Regulated By Mir-126-3p and Crucial For Memorymentioning
confidence: 99%
“…The cell-based functional screening was performed on the basis of the previous study (Lee et al, 2015). In the primary screening, HT22 cells were cotransfected with pEGFP-N1 and each of 120 cDNAs encoding endo-lysosomal proteins for 24 h and treated with 5 M oA␤ 1-42 for 36 h. Cells with apoptotic blebbing or shrunk morphology were regarded as dead cells.…”
Section: Cell-based Functional Screeningmentioning
confidence: 99%
“…Additionally, RHBDF1 was found to be a critical component of a molecular switch that regulates HIF1α stability under hypoxic conditions in breast cancer cells [ 18 ]. RHBDF1 expression is also involved in the activation of EGFR signalling during mouse embryonic development [ 19 ], in cancer predisposition syndrome [ 20 ], and in the regulation of proteasome activity under endoplasmic reticulum stress [ 21 ]. Moreover, the activity of RHBDF1 and its homolog RHBDF2 (iRhom2) has been reported to be important in promoting membrane trafficking and maturation of ADAM17, which is responsible for the proteolytic release and shedding of precursor proteins, including TGFα, on the cell surface [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, a genome wide screen identified iRhom1 as a stimulator of proteasome activity [31] and iRhom1 has been implicated in regulation of the hypoxic transcription factor Hif1 [32]. Notably, mice null for Hif1 exhibit vascular defects, as do ADAM17 KO mice [26].…”
Section: Mechanistic Roles Of Irhomsmentioning
confidence: 99%